Solar cell adhesive film and preparation method thereof

By setting a photonic crystal structure layer in the solar cell film and/or on the surface, the problem that the existing adhesive film cannot improve the photoelectric conversion efficiency of the solar cell is solved, the effect of increasing the solar light propagation path and absorption is achieved, and the photoelectric conversion efficiency of the solar cell is improved.

CN119529698APending Publication Date: 2025-02-28SHENZHEN HOLOKOOK TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411213029.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing adhesive film does not have the function of increasing the propagation path of sunlight in solar cells and enhancing the absorption of sunlight by solar cells, resulting in low photoelectric conversion efficiency of solar cells.

Method used

At least one photonic crystal structure layer is provided in and/or on the surface of the adhesive film body of the solar cell adhesive film. The photonic crystal structure layer is composed of a first material and a second material. The first material includes at least one of an upconversion material, a downconversion material and a perovskite material. The refractive index difference of the material is greater than or equal to 0.1.

Benefits of technology

By changing the light field distribution after the incident of sunlight, increasing the propagation path of sunlight in the solar cell, and using light diffraction to improve the photoelectric conversion efficiency of the solar cell. Compared with ordinary packaging films, the photoelectric conversion efficiency improvement value is at least 0.2%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529698A_ABST
    Figure CN119529698A_ABST
Patent Text Reader

Abstract

The invention discloses a solar cell adhesive film and a preparation method thereof, and relates to the technical field of adhesive film materials, the solar cell adhesive film comprises an adhesive film body and at least one photonic crystal structure layer located in the adhesive film body and / or on the surface of the adhesive film body; materials of the photonic crystal structure layer comprise a first material and a second material, the absolute value of the refractive index difference value of the first material and the second material is larger than or equal to 0.1, and the first material comprises at least one of an up-conversion material, a down-conversion material and a perovskite material. When the solar cell adhesive film provided by the invention is used as a packaging adhesive film of a solar cell, the light field distribution after sunlight incidence can be changed, the propagation path of sunlight in the solar cell is increased, and the effect of enhancing the photoelectric conversion efficiency of the solar cell is realized by utilizing light diffraction. The photonic crystal structure layer comprises at least one of an up-conversion material, a down-conversion material and a perovskite material, so that the photonic crystal structure layer can convert light in a wave band with relatively low absorption and utilization efficiency of the solar cell into light in a wave band with relatively high absorption and utilization efficiency; and the efficient absorption and utilization of sunlight in a wider wave band range by the solar cell are further enhanced. The two aspects are combined to improve the photoelectric conversion efficiency of the solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of adhesive film materials, and in particular to an adhesive film for solar cells and a preparation method thereof. Background Art

[0002] The solar photoelectric conversion efficiency of ordinary solar cells is still very low. There are two main reasons for the low photoelectric conversion efficiency of solar cells: the solar photons irradiated on the cell will be lost due to reflection or transmission, and the solar cell does not absorb photons below its bandgap width, and although it can absorb photons above its bandgap width, most of them are dissipated in the form of heat energy, which ultimately does not contribute to the photoelectric conversion efficiency.

[0003] At present, adhesive films (such as EVA films, etc.) are common packaging materials for solar cells, but existing adhesive films do not have the function of increasing the propagation path of sunlight in solar cells and enhancing the absorption of sunlight by solar cells, and cannot improve the photoelectric conversion efficiency of solar cells. Summary of the invention

[0004] Based on the above-mentioned deficiencies of the prior art, the purpose of the present invention is to provide a solar cell adhesive film and a preparation method thereof, aiming to solve the problem that the existing adhesive film does not have the function of increasing the propagation path of sunlight in solar cells and enhancing the absorption of sunlight by solar cells.

[0005] The technical solution of the present invention is as follows:

[0006] According to a first aspect of the present invention, there is provided a solar cell film, wherein the solar cell film comprises a film body, and at least one photonic crystal structure layer located in the film body and / or on the surface of the film body; the material of the photonic crystal structure layer comprises a first material and a second material, the absolute value of the refractive index difference between the first material and the second material is greater than or equal to 0.1, and the first material comprises at least one of an up-conversion material, a down-conversion material and a perovskite material.

[0007] Optionally, the thickness of the solar cell adhesive film is 200 μm to 5 mm; the thickness of the photonic crystal structure layer is 20 nm to 1000 μm;

[0008] When the photonic crystal structure layer is located in the adhesive film body, the thickness of the solar cell adhesive film is greater than the thickness of the photonic crystal structure layer.

[0009] Optionally, the material of the adhesive film body includes at least one of ethylene-vinyl acetate copolymer, polyolefin elastomer, polyethylene foam, polyurethane, silicone rubber, polyacrylate and polyester;

[0010] And / or, the second material includes at least one of an oxide material, a polymer material and a metal nanomaterial, and the oxide material includes ZrO2, Y2O3, Pr6O 11 , TiO2, ZnO, Al2O3, Fe2O3 and CeO2, the polymer material includes at least one of polystyrene, polymethyl methacrylate and liquid crystal polymer, and the metal nanomaterial includes at least one of gold nanoparticles and silver nanoparticles.

[0011] Optionally, the mass ratio of the first material to the second material is (1-8):(1-8).

[0012] Optionally, the photonic crystal structure layer includes randomly arranged photonic crystal structure units or periodically arranged photonic crystal structure units.

[0013] Optionally, the periodically arranged photonic crystal structure units include at least one of a honeycomb-arranged photonic crystal structure unit, a square-arranged photonic crystal structure unit, and a corner moiré superlattice-arranged photonic crystal structure unit.

[0014] Optionally, the photonic crystal structure layer includes at least one photonic crystal structure sub-layer, and the photonic crystal structure sub-layer is composed of arranged single photonic crystal structure units.

[0015] Optionally, the single photonic crystal structure unit is spherical.

[0016] Optionally, the up-conversion material comprises NaYF4:Yb 3+ ,Tm 3+ @TiO2、NaYF4:Yb 3+ ,Er 3+ 、YF3:Yb 3+ ,Er 3 + 、YOF:Yb 3+ ,Er 3+ 、NaYF4:Yb 3+ ,Er 3+ @SiO2@TiO2、NaYF4:Yb 3+ ,Er 3+ @TiO2 and NaYF4:Yb 3+ ,Er 3+ At least one of @SiO2@Au;

[0017] The down conversion material comprises at least one of an inorganic down conversion material and an organic fluorescent down conversion material, wherein the inorganic down conversion material comprises SrAlF5:Pr 3+ 、YF3:Pr 3+ 、NaYF4:Pr3+ 、CaAlF5:Pr 3+ 、NaMgF3:Pr 3+ 、KMgF3:Pr 3 + 、LaZrF7:Pr 3+ 、SrAl 12 O 19 :Pr 3+ 、LiYF4:Gd 3+ 、LiGdF4:Eu 3+ 、GdF3:Eu 3+ 、BaF2:Gd 3+ ,Eu 3+ 、LiGdF4:Er 3+ ,Tb 3+ , Zn2SiO4:Mn, Zn3(PO4)2:Mn, Cd3(PO4)2:Mn, Y2O3:Eu, YVO4:Eu, ZnS:Zn, ZnS:Ag, ZnS:Cu,Ag and ZnS:Cu,Al; the organic fluorescent down conversion material includes at least one of BUV 395, AF 350, AF 405, BV421, coumarin and coumarin derivatives;

[0018] The perovskite material includes at least one of an organic and inorganic mixed perovskite material and an all-inorganic perovskite material.

[0019] A second aspect of the present invention provides a method for preparing the solar cell adhesive film as described above, wherein the method for preparing the solar cell adhesive film comprises one of the following methods (1) to (7):

[0020] (1) forming a photonic crystal structure layer on the surface of the adhesive film body by micro-nano processing of the first material and the second material, thereby obtaining the solar cell adhesive film;

[0021] (2) forming a photonic crystal structure layer on the adhesive film body by self-assembly of the first material and the second material, thereby obtaining the solar cell adhesive film;

[0022] (3) forming a photonic crystal structure layer on the surface of the adhesive film body, and obtaining the adhesive film body containing the photonic crystal structure layer after hot pressing, thereby obtaining the solar cell adhesive film;

[0023] (4) mixing the first material, the second material, the polymer material for the adhesive film body and the solvent, spraying or coating, and then drying and curing to form an adhesive film body containing a photonic crystal structure layer, thereby obtaining the solar cell adhesive film;

[0024] (5) Mixing the first material, the second material, the polymer material for the adhesive film body and the solvent, and spraying or scraping to form an adhesive film body containing a photonic crystal structure layer, and then forming another photonic crystal structure layer on the surface of the adhesive film body by method (1) or method (2), thereby obtaining the solar cell adhesive film;

[0025] (6) heating the polymer material of the adhesive film body until it is melted, and then mixing it with the first material and the second material, and forming an adhesive film body containing a photonic crystal structure layer inside after spraying, scraping or extrusion, thereby obtaining the solar cell adhesive film;

[0026] (7) The polymer material of the adhesive film body is heated until it is melted, and then mixed with the first material and the second material. After spraying, scraping or extrusion, a film body containing a photonic crystal structure layer is formed. Then, another photonic crystal structure layer is formed on the surface of the film body by method (1) or method (2), thereby obtaining the solar cell adhesive film.

[0027] Optionally, the polymer material for the adhesive film body includes at least one of ethylene-vinyl acetate copolymer, polyolefin elastomer, polyethylene foam, polyurethane, silicone rubber, polyacrylate and polyester;

[0028] The solvent comprises at least one of toluene, xylene, ethyl acetate, ethanol, acetone, hexane methanol and water;

[0029] The drying and curing temperature is 70 to 150° C., and the drying and curing time is 0.5 to 3 hours.

[0030] Beneficial effects: The light transmittance of the solar cell adhesive film provided by the present invention can be greater than 85%, and the peel strength is greater than 5N / mm. It can not only be used as a solar cell packaging adhesive film, but also the present invention sets a photonic crystal structure layer in the adhesive film body and / or on the surface of the adhesive film body, which can change the light field distribution after the incident sunlight, increase the propagation path of sunlight in the solar cell, and use the diffraction of light to enhance the photoelectric conversion efficiency of the solar cell. In addition, since the first material in the photonic crystal structure layer includes at least one of an up-conversion material, a down-conversion material, and a perovskite material, it can convert light in a band with a lower absorption and utilization efficiency of the solar cell into light in a band with a higher absorption and utilization efficiency, further enhancing the efficient absorption and utilization of sunlight in a wider band by the solar cell. The combined effect of the two aspects improves the photoelectric conversion efficiency of the solar cell. Compared with solar cells using ordinary packaging adhesive films, the photoelectric conversion efficiency of solar cells using the solar cell adhesive film provided by the present invention is improved by at least 0.2%. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1Schematic diagram of the structure of the first solar cell adhesive film in an embodiment of the present invention.

[0032] Figure 2 Schematic diagram of the structure of the second solar cell adhesive film in an embodiment of the present invention.

[0033] Figure 3 Schematic diagram of the structure of the third solar cell adhesive film in an embodiment of the present invention.

[0034] Figure 4 Schematic diagram of the structure of the fourth solar cell adhesive film in an embodiment of the present invention.

[0035] Figure 5 Schematic diagram of a photonic crystal structure layer containing photonic crystal structure units arranged in a honeycomb pattern.

[0036] Figure 6 Schematic diagram of a photonic crystal structure layer containing photonic crystal structure units arranged in a square shape.

[0037] Figure 7 Schematic diagram of a photonic crystal structure layer containing a single layer of non-close-packed photonic crystal structure units.

[0038] Figure 8 Schematic diagram of a photonic crystal structure layer containing two layers of non-close-packed photonic crystal structure units.

[0039] Fig. 9 Schematic diagram of a photonic crystal structure layer containing two layers of close-packed photonic crystal structure units.

[0040] Fig.10 Schematic diagram of a photonic crystal structure layer containing three layers of close-packed photonic crystal structure units.

[0041] Fig.11 Schematic diagram of a photonic crystal structure layer containing a rotation moiré superlattice photonic crystal structure unit.

[0042] Fig.12 This is a schematic diagram of applying the solar cell adhesive film to the solar cell in Example 1. DETAILED DESCRIPTION

[0043] The present invention provides a solar cell adhesive film and a preparation method thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0044] Unless otherwise defined, all technical terms and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0045] An embodiment of the present invention provides a solar cell film, wherein the solar cell film includes a film body and at least one photonic crystal structure layer located in the film body and / or on the surface of the film body; the material of the photonic crystal structure layer includes a first material and a second material, the absolute value of the refractive index difference between the first material and the second material is greater than or equal to 0.1, and the first material includes at least one of an up-conversion material, a down-conversion material and a perovskite material.

[0046] In the embodiment of the present invention, the photonic crystal structure layer can be located on the surface of the adhesive film body (one surface or two surfaces), in the adhesive film body, or on the surface of the adhesive film body and in the adhesive film body. The photonic crystal structure layer can be one layer, two layers, three layers, etc.

[0047] Specifically, in some embodiments, Figure 1 As shown, the solar cell adhesive film 1 includes an adhesive film body 11 and a photonic crystal structure layer 12, wherein the photonic crystal structure layer 12 is located in the adhesive film body 11. Of course, the adhesive film body may also contain two or more photonic structure layers.

[0048] In some embodiments, Figure 2 As shown, the solar cell adhesive film 1 includes an adhesive film body 11 and a photonic crystal structure layer 12 , and the photonic crystal structure layer 12 is located on the surface of the adhesive film body 11 .

[0049] In some embodiments, Figure 3 As shown, the solar cell adhesive film 1 includes an adhesive film body 11 and two photonic crystal structure layers 12 , wherein the two photonic crystal structure layers 12 are respectively located on the surface of the adhesive film body 11 and in the adhesive film body 11 .

[0050] In some embodiments, Figure 4 As shown, the solar cell adhesive film 1 includes an adhesive film body 11 and two photonic crystal structure layers 12 , and the two photonic crystal structure layers 12 are respectively located on the upper surface and the lower surface of the adhesive film body.

[0051] The solar cell film provided by the embodiment of the present invention has a light transmittance greater than 85% and a peel strength greater than 5N / mm. It can not only be used as a packaging film for solar cells, but also a photonic crystal structure layer (a first material and a second material having an absolute value of a refractive index difference greater than or equal to 0.1 are used together to form a photonic crystal structure layer) in the film body and / or on the surface of the film body in the embodiment of the present invention, which can change the light field distribution after the incident sunlight, increase the propagation path of sunlight in the solar cell, and use the diffraction of light to enhance the photoelectric conversion efficiency of the solar cell. In addition, since the first material in the photonic crystal structure layer includes at least one of an up-conversion material, a down-conversion material, and a perovskite material, it can convert light in a band with a lower absorption and utilization efficiency of the solar cell into light in a band with a higher absorption and utilization efficiency, further enhancing the efficient absorption and utilization of sunlight in a wider band by the solar cell. The two aspects work together to improve the photoelectric conversion efficiency of the solar cell. Compared with a solar cell using an ordinary packaging film, the photoelectric conversion efficiency of the solar cell using the solar cell film provided by the present invention is improved by at least 0.2%.

[0052] In some embodiments, the thickness of the solar cell adhesive film is 200 μm to 5 mm, for example, 200 μm, 300 μm, 400 μm, 500 μm, 800 μm, 1 mm, 2 mm, 3 mm, 4 mm or 5 mm, etc.; the thickness of the photonic crystal structure layer is 20 nm to 1000 μm, for example, 20 nm, 50 nm, 100 nm, 200 nm, 500 nm, 800 nm, 1 μm, 5 μm, 10 μm, 100 μm, 200 μm, 500 μm, 800 μm or 1000 μm. When the photonic crystal structure layer is located in the adhesive film body, the thickness of the solar cell adhesive film is greater than the thickness of the photonic crystal structure layer. For example, when the thickness of the solar cell adhesive film is 200 μm, the thickness of the photonic crystal structure layer is 20 nm, 50 nm, 100 nm, 200 nm, 500 nm, 800 nm, 1 μm, 5 μm, 10 μm or 100 μm, etc.

[0053] In some embodiments, the material of the adhesive film body includes at least one of ethylene-vinyl acetate copolymer (EVA), polyolefin elastomer (POE), polyethylene foam (EPE), polyurethane, silicone rubber, polyacrylate and polyester, but is not limited thereto.

[0054] In some embodiments, the photonic crystal structure layer includes randomly arranged photonic crystal structure units or periodically arranged photonic crystal structure units.

[0055] In some embodiments, the periodically arranged photonic crystal structure units include honeycomb-arranged photonic crystal structure units (eg Figure 5 As shown, Figures 5 to 11 A small ball in the middle can be represented as a photonic crystal structure unit), a square-arranged photonic crystal structure unit (such as Figure 6 As shown), photonic crystal structure units arranged in a corner moiré superlattice structure (such as Fig.11 In this way, the periodically arranged photonic crystal structure units can produce a bandgap effect on light waves, thereby achieving control over the propagation direction of light. This makes the photonic crystal structure have higher optical performance, lower transmittance, higher absorptivity and scattering for specific light.

[0056] In some embodiments, the photonic crystal structure layer includes at least one photonic crystal structure sublayer, and the photonic crystal structure sublayer is composed of a single photonic crystal structure unit. When the photonic crystal structure layer includes one photonic crystal structure sublayer, Figures 5 to 7 As shown, it may include a single layer of closely packed photonic crystal structural units ( Figure 5 and Figure 6 As shown), it may also include a single layer of non-close-packed photonic crystal structural units (such as Figure 7 When the photonic crystal structure layer includes multiple layers of photonic crystal structure sublayers, it may include two layers of non-close-packed photonic crystal structure units (such as Figure 8 As shown), it may also include two layers of closely packed photonic crystal structural units (such as Fig. 9 As shown), it may also include three layers of closely packed photonic crystal structural units (such as Fig.10 As shown), it may also include a photonic crystal structure unit (such as Fig.11 shown).

[0057] In some embodiments, the single photonic crystal structure unit is spherical. The particle size of each photonic crystal structure unit is 20nm to 1μm, for example, it can be 20nm, 50nm, 100nm, 150nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm or 1μm. Such a suitable particle size range can improve the light absorption rate and scattering characteristics of the photonic crystal structure layer.

[0058] In some embodiments, the mass ratio of the first material to the second material is (1-8):(1-8). In some embodiments, the mass ratio of the first material to the second material is (1-2):(1-8) or (1-8):(1-2). For example, the mass ratio of the first material to the second material is 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1 or 8:1, etc.

[0059] In some embodiments, the second material includes at least one of an oxide material, a polymer material, and a metal nanomaterial, and the oxide material includes ZrO2, Y2O3, Pr6O 11 , TiO2, ZnO, Al2O3, Fe2O3 and CeO2, but not limited thereto; the polymer material includes at least one of polystyrene, polymethyl methacrylate and liquid crystal polymer (such as cyanate liquid crystal polymer), but not limited thereto; the metal nanomaterial includes at least one of gold nanoparticles and silver nanoparticles, but not limited thereto.

[0060] In some embodiments, the upconversion material includes but is not limited to NaYF4:Yb 3+ ,Tm 3+ @TiO2 (For its preparation method, please refer to β-NaYF4:Yb 3+ ,Tm 3+ @TiO2 core-shell nanoparticles incorporated into themesoporous layer for high efficiency perovskite solar cells, Liang, Jiwei, "Electrochimica Acta"), NaYF4:Yb 3+ ,Er 3+ 、YF3:Yb 3+ ,Er 3+ 、YOF:Yb 3+ ,Er 3+ 、NaYF4:Yb 3+ ,Er 3+ @SiO2@TiO2 (the preparation method is shown in Performance optimization in dye-sensitized solar cells with beta-NaYF4:Yb 3+ ,Er 3+@SiO2@TiO2 mesoporous microspheres as multi-functional photoanodes, Zhu, Yihua, "Electrochimica Acta"), NaYF4:Yb 3+ ,Er 3+ @SiO2@Au (For its preparation method, please refer to Multifunctional NaYF4:Yb 3+ ,Er 3+ @SiO2@Au heterogeneous nanocomposites for upconversion luminescence,temperature sensing and photothermal conversion, DLi, "Rsc Advances").

[0061] In some embodiments, the down conversion material comprises at least one of an inorganic down conversion material and an organic fluorescent down conversion material, wherein the inorganic down conversion material comprises SrAlF5:Pr 3+ (This material is Pr 3+ doped SrAlF5, the meaning of similarly expressed materials in the present invention is analogous), YF3:Pr 3+ 、NaYF4:Pr 3+ 、CaAlF5:Pr 3+ 、NaMgF3:Pr 3+ 、KMgF3:Pr 3+ 、LaZrF7:Pr 3+ 、SrAl 12 O 19 :Pr 3+ 、LiYF4:Gd 3+ 、LiGdF4:Eu 3+ 、GdF3:Eu 3+ 、BaF2:Gd 3+ ,Eu 3+ 、LiGdF4:Er 3+ ,Tb 3+, at least one of Zn2SiO4:Mn, Zn3(PO4)2:Mn, Cd3(PO4)2:Mn, Y2O3:Eu, YVO4:Eu, ZnS:Zn, ZnS:Ag, ZnS:Cu,Ag, ZnS:Cu,Al; the organic fluorescence down-conversion material includes at least one of BUV 395 (i.e., Brilliant Ultra Violet 395, available from ThermoFisher scientific), AF350 (i.e., Alexa Fluor 350, available from Duofluo Biotechnology), AF 405 (i.e., Alexa Fluor 405, available from Duofluo Biotechnology), BV 421 (i.e., Brilliant Ultra Violet 421, available from ThermoFisher scientific), coumarin and coumarin derivatives.

[0062] In some embodiments, the perovskite material includes at least one of an organic-inorganic hybrid perovskite material and an all-inorganic perovskite material. The organic-inorganic hybrid perovskite material includes at least one of CH3NH3PbBr3, CH3NH3PbI3, CH3NH3PbI 3-x Br x (0 < x < 3); the all-inorganic perovskite material includes at least one of perovskite sulfide (e.g., CsPbS3), perovskite selenide (e.g., CsPbSe3), perovskite lead ferrite (e.g., PbFeO3), perovskite bismuth ferrite (e.g., BiFeO3), perovskite oxide (e.g., CaTiO3).

[0063] The embodiment of the present invention also provides a method for preparing the solar cell encapsulant film as described above in the embodiments of the present invention. Among them, the method for preparing the solar cell encapsulant film includes one of the following methods (1) to (7):

[0064] (1) Form a photonic crystal structure layer on the surface of the encapsulant film body by means of micro-nano processing (precision coating, vacuum coating, photolithography, etc.) for the first material and the second material, and then obtain the solar cell encapsulant film;

[0065] (2) Form a photonic crystal structure layer on the encapsulant film body by means of self-assembly for the first material and the second material, and then obtain the solar cell encapsulant film.

[0066] (3) Form a photonic crystal structure layer on the surface of the encapsulant film body, and after hot pressing, obtain an encapsulant film body containing a photonic crystal structure layer inside, and then obtain the solar cell encapsulant film;

[0067] (4) mixing the first material, the second material, the polymer material for the adhesive film body and the solvent, spraying or coating, and then drying and curing to form an adhesive film body containing a photonic crystal structure layer, thereby obtaining the solar cell adhesive film;

[0068] (5) Mixing the first material, the second material, the polymer material for the adhesive film body and the solvent, and spraying or scraping to form an adhesive film body containing a photonic crystal structure layer, and then forming another photonic crystal structure layer on the surface of the adhesive film body by method (1) or method (2), thereby obtaining the solar cell adhesive film;

[0069] (6) heating the polymer material of the adhesive film body until it is melted, and then mixing it with the first material and the second material, and forming an adhesive film body containing a photonic crystal structure layer inside after spraying, scraping or extrusion, thereby obtaining the solar cell adhesive film;

[0070] (7) The polymer material of the adhesive film body is heated until it is melted, and then mixed with the first material and the second material. After spraying, scraping or extrusion, a film body containing a photonic crystal structure layer is formed. Then, another photonic crystal structure layer is formed on the surface of the film body by method (1) or method (2), thereby obtaining the solar cell adhesive film.

[0071] The selection of the first material and the second material is as described above.

[0072] The preparation method provided by the present invention is simple, and the prepared solar cell adhesive film has high light transmittance and strong peel strength. As an encapsulation film for solar cells, it can increase the propagation path of sunlight in the solar cell, enhance the solar cell's absorption of sunlight, and increase the photoelectric conversion efficiency of the solar cell.

[0073] In method (1), in some embodiments, the micro-nano processing method is photolithography, specifically, the first material and the second material are mixed and applied to the film body by spin coating or spraying (such as inkjet coating) to form a film, and then photolithography is performed to form a photonic crystal structure layer on the film body.

[0074] Furthermore, method (1) specifically comprises the following steps:

[0075] Adding the first material and the second material into a polyvinyl alcohol (PVA) aqueous solution for ultrasonic dispersion to obtain a dispersion;

[0076] The dispersion is spin-coated or spray-coated on the adhesive film body, and after drying (for example, drying in a dryer at 80°C), laser etching is performed using a mask (depending on the shape of the mask, a photonic crystal structure layer containing different photonic crystal structure unit arrangements is obtained) (process parameters are: power 10-50W, laser pulse width 1-10 nanoseconds, laser pulse frequency 1-1000Hz, defocusing amount 0.01-0.1mm, auxiliary gas is argon or helium) to form a photonic crystal structure layer on the adhesive film body.

[0077] In some embodiments, the first material and the second material are coated on the adhesive film body by precision coating, and after drying at 60-120° C., a photonic crystal structure layer is formed on the adhesive film body.

[0078] In some embodiments, the first material and the second material are formed into a photonic crystal structure layer on the film body by nanoimprinting or two-photon printing.

[0079] In method (2), in some embodiments, the step of forming a photonic crystal structure layer on the adhesive film body by self-assembly of the first material and the second material specifically includes:

[0080] The first material, the second material and a surfactant are added to a polyvinyl alcohol (PVA) aqueous solution for ultrasonic dispersion to obtain a dispersion; wherein the surfactant includes at least one of anionic surfactants, cationic surfactants, amphoteric surfactants and nonionic surfactants; the anionic surfactant includes at least one of alkylbenzene sulfonates (such as ammonium dodecylbenzenesulfonate), α-olefin sulfonates, and alkyl sulfonates; the cationic surfactant includes at least one of hexadecyltrimethylammonium chloride and octadecyldimethylbenzylammonium chloride; the amphoteric surfactant includes at least one of dodecylaminopropionic acid, sulfobetaine and phosphate betaine; the nonionic surfactant includes at least one of glycerol fatty acid esters, sorbitan fatty acid esters, polyoxyethylene fatty alcohol ethers and fatty acid sorbitan;

[0081] The dispersion is coated on the adhesive film body, and after drying, an appropriate amount of charge is applied using an electrostatic voltage of 15 to 25 kV for 5 to 10 minutes to automatically assemble the first material and the second material into a specific structure, forming a photonic crystal structure layer on the adhesive film body.

[0082] Of course, the dispersion is coated on the adhesive film body, and after DLP (digital light processing) chip projection, exposure and development, multi-layer photocuring is performed to form a photonic crystal structure layer on the adhesive film body.

[0083] In method (3), in some embodiments, a photonic crystal structure layer can be formed on the adhesive film body by method (1) or method (2), and then after hot pressing, the photonic crystal structure layer enters into the adhesive film body to form an adhesive film body containing the photonic crystal structure layer.

[0084] In method (4) and method (5), in some embodiments, the solvent includes at least one of toluene, xylene, ethyl acetate, ethanol, acetone, hexane methanol and water.

[0085] In some embodiments, the drying and curing temperature is 70-150°C (for example, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C, etc.), and the drying and curing time is 0.5-3h (for example, 0.5h, 1h, 1.5h, 2h, 2.5h or 3h, etc.).

[0086] In methods (6) and (7), in some embodiments, the step of heating the polymer material of the adhesive film body until it is melted, then mixing it with the first material and the second material, and spraying, scraping or extruding it to form the adhesive film body containing the photonic crystal structure layer comprises:

[0087] The first material, the second material, the polymer material for the adhesive film body and the auxiliary agent (specifically, a cross-linking agent for curing the polymer material for the adhesive film to improve the heat resistance and weather resistance of the adhesive film) are placed in a heating device and heated until the polymer is melted to obtain a molten mixture;

[0088] Then the molten mixture is coated by a doctor blade coater (process parameters are: coating speed of 1 to 10 m / min; coating temperature of 20 to 80° C.; pressure of 10 to 500 Pa), and after cooling at room temperature for 0.5 to 3 hours, a film body containing a photonic crystal structure layer is obtained; or,

[0089] The first material, the second material, the polymer material for the film body and the additives (the selection of the additives is as described above) are added into the extruder, and the film is extruded through heating of the extruder and rotation of the screw (the specific process parameters are: extrusion temperature of 150-350°C, screw speed of 10-100rpm, extrusion pressure of 10-500Pa, and mold temperature of 100-200°C).

[0090] In methods (1) to (7), the polymer material used for the adhesive film body includes at least one of ethylene-vinyl acetate copolymer, polyolefin elastomer, polyethylene foam, polyurethane, silicone rubber, polyacrylate and polyester.

[0091] The present invention will be further described below by means of specific examples.

[0092] Example 1

[0093] This embodiment provides a solar cell adhesive film and a preparation method thereof, such as Figure 2 As shown, the solar cell adhesive film 1 includes an adhesive film body 11 and a photonic crystal structure layer 12 located on the surface of the adhesive film body 11 (the structure of the photonic crystal structure layer is as shown in FIG. Figure 6 As shown), the adhesive film body is an EVA adhesive film body, the thickness of the adhesive film body is 1 mm, and the material of the photonic crystal structure layer is NaYF4:Yb with a mass ratio of 1:1 3+ ,Er 3+ @SiO2@Au and Al2O3 (the preparation method thereof is described above), the thickness of the photonic crystal structure layer is 1000nm (ie the particle size of each photonic crystal structure unit is 1000nm).

[0094] The preparation method of the solar cell adhesive film comprises the following steps:

[0095] Provide EVA film body with a thickness of 1mm;

[0096] 1g of NaYF4:Yb 3+ ,Er 3+ @SiO2@Au (the preparation method thereof is as described above, wherein NaYF4, Yb 3+ With Er 3+ The molar ratio of 78:20:2) and 1g of Al2O3 are added into 100g of polyvinyl alcohol (PVA) aqueous solution (PVA mass content is 80%) for ultrasonic dispersion to obtain a dispersion;

[0097] The dispersion is spin-coated on the EVA film body, dried (for example, placed in a dryer at 80°C), and then a mask (with the same shape as the EVA film) is used. Figure 6 Correspondingly) laser etching is performed (process parameters are power 25 W; laser pulse width is 5 nanoseconds (ns); laser pulse frequency is 500 Hz; defocus amount is 0.05 mm; auxiliary gas is argon) to form a photonic crystal structure layer with a thickness of 1000 nm on the EVA film body.

[0098] The photoelectric conversion efficiency was tested, and the results are shown in Table 1.

[0099] like Fig.12As shown, the solar cell adhesive film 1 in Example 1 is set on the monocrystalline silicon solar cell 2 as an encapsulation adhesive film, which can increase the propagation path of sunlight in the solar cell and play a role in diffraction and spectroscopy, forming a solar cell module with a photoelectric conversion efficiency of 25.75%. The ordinary EVA adhesive film with a thickness of 1 mm is set on the monocrystalline silicon solar cell 2 as an encapsulation adhesive film, forming a solar cell module with a photoelectric conversion efficiency of 25%.

[0100] Table 1. Performance results of solar cell adhesive film in Example 1

[0101]

[0102] Example 2

[0103] This embodiment provides a solar cell adhesive film and a preparation method thereof, which is different from the embodiment 1 in that the material of the photonic crystal structure layer includes a first material and a second material in a mass ratio of 1:1, wherein the first material is NaYF4:Yb 3+ ,Er 3+ @SiO2@Au (the material is the same as that in Example 1) and ZnS:Cu,Al (wherein the molar ratio of Cu to Zn is 0.0003:1, and the molar ratio of Cu to Al is 0.5:1. For its specific preparation method, see "Preparation of ZnS:Cu, Al Nano X-ray Luminescent Powder by Hydrothermal Method and Its Spectral Characteristics, Xin Mei et al., Journal of Chemistry in Universities"), and the second material is ZnO.

[0104] 0.5 g of NaYF4:Yb 3+ ,Er 3+ @SiO2@Au, 0.5 g of ZnS:Cu,Al and 1 g of Al2O3 were added to 100 g of polyvinyl alcohol (PVA) aqueous solution (PVA mass content was 80%) and ultrasonically dispersed to obtain a dispersion.

[0105] The photoelectric conversion efficiency was tested and the results are shown in Table 2.

[0106] When the solar cell film in Example 2 is used as the packaging film for monocrystalline silicon solar cells, the photoelectric conversion efficiency of the solar cell module formed is 25.78%; when the ordinary EVA film with a thickness of 1 mm is used as the packaging film for monocrystalline silicon solar cells, the photoelectric conversion efficiency of the solar cell module formed is 25.5%.

[0107] Table 2 Performance results of solar cell adhesive film in Example 2

[0108]

[0109] In summary, the present invention provides a solar cell adhesive film and a preparation method thereof. The light transmittance of the solar cell adhesive film provided by the present invention can be greater than 85%, and the peel strength is greater than 5N / mm. It can not only be used as a solar cell packaging adhesive film, but also the present invention sets a photonic crystal structure layer in the adhesive film body and / or on the surface of the adhesive film body, which can change the light field distribution after the incident sunlight, increase the propagation path of sunlight in the solar cell, and use the diffraction of light to enhance the photoelectric conversion efficiency of the solar cell. In addition, since the first material in the photonic crystal structure layer includes at least one of an up-conversion material, a down-conversion material, and a perovskite material, it can convert the light in the band with a lower absorption and utilization efficiency of the solar cell into the light in the band with a higher absorption and utilization efficiency, and further enhance the efficient absorption and utilization of sunlight in a wider band by the solar cell. The two aspects work together to improve the photoelectric conversion efficiency of the solar cell. Compared with solar cells using ordinary packaging adhesive films, the photoelectric conversion efficiency of solar cells using the solar cell adhesive film provided by the present invention is improved by at least 0.2%.

[0110] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A solar cell adhesive film, characterized in that: The solar cell adhesive film includes an adhesive film body, and at least one photonic crystal structure layer located in the adhesive film body and / or on the surface of the adhesive film body; the material of the photonic crystal structure layer includes a first material and a second material, the absolute value of the refractive index difference between the first material and the second material is greater than or equal to 0.1, and the first material includes at least one of an up-conversion material, a down-conversion material and a perovskite material.

2. The solar cell adhesive film according to claim 1, characterized in that: The thickness of the solar cell adhesive film is 200 μm to 5 mm; the thickness of the photonic crystal structure layer is 20 nm to 1000 μm; When the photonic crystal structure layer is located in the adhesive film body, the thickness of the solar cell adhesive film is greater than the thickness of the photonic crystal structure layer.

3. The solar cell adhesive film according to claim 1, characterized in that: The material of the adhesive film body includes at least one of ethylene-vinyl acetate copolymer, polyolefin elastomer, polyethylene foam, polyurethane, silicone rubber, polyacrylate and polyester; And / or, the second material includes at least one of an oxide material, a polymer material and a metal nanomaterial, and the oxide material includes ZrO2, Y2O3, Pr6O 11 , TiO2, ZnO, Al2O3, Fe2O3 and CeO2, the polymer material includes at least one of polystyrene, polymethyl methacrylate and liquid crystal polymer, and the metal nanomaterial includes at least one of gold nanoparticles and silver nanoparticles.

4. The solar cell adhesive film according to claim 1, characterized in that: The mass ratio of the first material to the second material is (1-8):(1-8).

5. The solar cell adhesive film according to claim 1, characterized in that: The photonic crystal structure layer includes randomly arranged photonic crystal structure units or periodically arranged photonic crystal structure units.

6. The solar cell adhesive film according to claim 5, characterized in that: The periodically arranged photonic crystal structure units include at least one of a honeycomb-arranged photonic crystal structure unit, a square-arranged photonic crystal structure unit, and a corner moiré superlattice-arranged photonic crystal structure unit.

7. The solar cell adhesive film according to claim 5, characterized in that: The photonic crystal structure layer includes at least one photonic crystal structure sublayer, and the photonic crystal structure sublayer is formed by arranging single photonic crystal structure units.

8. The solar cell adhesive film according to claim 7, characterized in that: The single photonic crystal structure unit is spherical.

9. The solar cell adhesive film according to claim 1, characterized in that: The up-conversion material includes NaYF4:Yb 3 + ,Tm 3+ @TiO2、NaYF4:Yb 3+ ,Er 3+ 、YF3:Yb 3+ ,Er 3+ 、YOF:Yb 3+ ,Er 3+ 、NaYF4:Yb 3+ ,Er 3+ @SiO2@TiO2、NaYF4:Yb 3+ ,Er 3+ @TiO2 and NaYF4:Yb 3+ ,Er 3+ At least one of @SiO2@Au; The down conversion material comprises at least one of an inorganic down conversion material and an organic fluorescent down conversion material, wherein the inorganic down conversion material comprises SrAlF5:Pr 3+ 、YF3:Pr 3+ 、NaYF4:Pr 3+ 、CaAlF5:Pr 3+ 、NaMgF3:Pr 3+ 、KMgF3:Pr 3+ 、LaZrF7:Pr 3+ 、SrAl 12 O 19 :Pr 3+ 、LiYF4:Gd 3+ 、LiGdF4:Eu 3+ 、GdF3:Eu 3+ 、BaF2:Gd 3+ ,Eu 3+ 、LiGdF4:Er 3 + ,Tb 3+ , Zn2SiO4:Mn, Zn3(PO4)2:Mn, Cd3(PO4)2:Mn, Y2O3:Eu, YVO4:Eu, ZnS:Zn, ZnS:Ag, ZnS:Cu,Ag and ZnS:Cu,Al; the organic fluorescent down conversion material includes at least one of BUV 395, AF 350, AF 405, BV421, coumarin and coumarin derivatives; The perovskite material includes at least one of an organic and inorganic mixed perovskite material and an all-inorganic perovskite material.

10. A method for preparing the solar cell adhesive film according to claim 1, characterized in that: The method for preparing the solar cell adhesive film comprises one of the following methods (1) to (7): (1) forming a photonic crystal structure layer on the surface of the adhesive film body by micro-nano processing of the first material and the second material, thereby obtaining the solar cell adhesive film; (2) forming a photonic crystal structure layer on the adhesive film body by self-assembly of the first material and the second material, thereby obtaining the solar cell adhesive film; (3) forming a photonic crystal structure layer on the surface of the adhesive film body, and obtaining the adhesive film body containing the photonic crystal structure layer after hot pressing, thereby obtaining the solar cell adhesive film; (4) mixing the first material, the second material, the polymer material for the adhesive film body and the solvent, spraying or coating, and then drying and curing to form an adhesive film body containing a photonic crystal structure layer, thereby obtaining the solar cell adhesive film; (5) Mixing the first material, the second material, the polymer material for the adhesive film body and the solvent, and spraying or scraping to form an adhesive film body containing a photonic crystal structure layer, and then forming another photonic crystal structure layer on the surface of the adhesive film body by method (1) or method (2), thereby obtaining the solar cell adhesive film; (6) heating the polymer material of the adhesive film body until it is melted, and then mixing it with the first material and the second material, and forming an adhesive film body containing a photonic crystal structure layer inside after spraying, scraping or extrusion, thereby obtaining the solar cell adhesive film; (7) The polymer material of the adhesive film body is heated until it is melted, and then mixed with the first material and the second material. After spraying, scraping or extrusion, a film body containing a photonic crystal structure layer is formed. Then, another photonic crystal structure layer is formed on the surface of the film body by method (1) or method (2), thereby obtaining the solar cell adhesive film.

11. The preparation method according to claim 10, characterized in that: The polymer material of the adhesive film body includes at least one of ethylene-vinyl acetate copolymer, polyolefin elastomer, polyethylene foam, polyurethane, silicone rubber, polyacrylate and polyester; The solvent comprises at least one of toluene, xylene, ethyl acetate, ethanol, acetone, hexane methanol and water; The drying and curing temperature is 70 to 150° C., and the drying and curing time is 0.5 to 3 hours.